Gli strumenti della scrittura: un confronto metapoetico tra Valerio Magrelli e Pierluigi Cappello (ENTHYMEMA, 2020)
This article compares the metapoetic works on the act of writing by Valerio Magrelli (Roma, 1975) and by Pierluigi Cappello (Gemona del Friuli, 1967 – Cassacco, 2017). After studying and sampling the metapoetic vocabulary of each author, I selected specific terms that occurred in both authors’ poems about the act of writing by hand: paper, rubber, pencil, page, and notebook. Therefore, this corpus consists of poems that include at least one of these nouns. The metric and rhetorical analysis of these poems allowed me not only to identify specific features for each author, but also to observe some analogies, such as the creation of a world existing “inside the poem” – a world that shelters and at the same time imprisons the “poetic I” of the authors.
Keywords: metapoetic lexicon; Valerio Magrelli; Pierluigi Cappello; writing; pencil; laboratory; world